2021
DOI: 10.3390/ani11020342
|View full text |Cite
|
Sign up to set email alerts
|

Canine Blood Group Prevalence and Geographical Distribution around the World: An Updated Systematic Review

Abstract: In recent years, blood transfusions have been more commonly given to pets. The importance of determining blood groups in dogs and cats is, therefore, well-known for reducing the risk of adverse reactions in the recipient blood caused by a “non-compatible” donor. This systematic review summarizes data from previously published reports and follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for systematic reviews. After applying the inclusion and exclusion criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…As in dogs, to determine the DEA group [ 24 ], several methods have been proposed to determine the blood group in cats [ 5 , 25 ]. Feline blood typing can be performed: (i) by a point-of-care test (CARD) consisting of a card with wells that contain lyophilized monoclonal anti-A or anti-B antibody [ 26 ]; (ii) by a point-of-care test (CHROM) based on immunochromatographic diffusion of RBCs with monoclonal anti-A and anti-B antibodies (DME VET A + B, provided by Alvedia, Lyon, France) [ 27 , 28 ]; (iii) by a technique (GEL) method based on gel columns containing anti-A antibodies [ 29 ]; (iv) by a SLIDE test and tube assay (TUBE) in which the degree of agglutination is scored as for the CARD method [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As in dogs, to determine the DEA group [ 24 ], several methods have been proposed to determine the blood group in cats [ 5 , 25 ]. Feline blood typing can be performed: (i) by a point-of-care test (CARD) consisting of a card with wells that contain lyophilized monoclonal anti-A or anti-B antibody [ 26 ]; (ii) by a point-of-care test (CHROM) based on immunochromatographic diffusion of RBCs with monoclonal anti-A and anti-B antibodies (DME VET A + B, provided by Alvedia, Lyon, France) [ 27 , 28 ]; (iii) by a technique (GEL) method based on gel columns containing anti-A antibodies [ 29 ]; (iv) by a SLIDE test and tube assay (TUBE) in which the degree of agglutination is scored as for the CARD method [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that there are over 400,000 possible equine blood types due to varying permutations of blood systems and factors (Proverbio et al, 2020), and the blood phenotype of cattle has even been suggested to be analogous to fingerprints (Humble, 1954). In comparison, 60% of dogs worldwide are of DEA 1 (Elbelt et al, 2020; Mangiaterra et al, 2021) and 80%–95% of nonpedigree cats are of feline blood type A (Juvet et al, 2011; McDermott et al, 2020; Vieira et al, 2017). Due to the limited sample size of our study, it is possible that the number of different crossmatching patterns of killer whales, and by extension erythrocyte antigens (that were not examined here), is likely underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion medicine is a specialized branch of medicine now widely applied in veterinary clinical practice too, in which animals (especially dogs, cats, and horses) can receive life-saving blood transfusions that may be necessary, following major blood loss due to traumas, surgery, anemias, and coagulopathies of various origins [29,[108][109][110][111][112][113]. Compared to humans, a few articles are present regarding SLs in blood units from veterinary species.…”
Section: Omics Technologies In Veterinary Transfusion Medicinementioning
confidence: 99%